KOMIK DI LINGKARAN INDUSTRI MUSIK - Terra Bajraghosa (DeKaVe, 2011)
Comic ges. Based on comprehention as a narrative media, comics in Indonesia are oftenly compared to bas-reliefs on Borobudur temple and Wayang Beber.. From many kind of stories Indonesian comic books recently offered, with the developed visual wrapping, some comics steal attentions by its unique themes. These comic books are created because of the inspiration and relation to music industry. These comic books couldn't be seen from the visual style alone, as they were created in many visual genres, but they could be seen from their relations to music industry, whether the mainstream or indie ones. These comic books are published together with the music CDs, telling fictional stories from factual bands or musicians, telling a band's factual stories, or created by one of the band members. To understand modes of creation of these music industry-related-comic books, visual narrative approach will be applied. Through visual narrative approach, the band members' or musician's necessity for telling stories via comics, beside the common practices via music and song lyrics, will be observed.Keywords : Comic book, music industry, visual narrative